Household Leverage and Stock Market Investment Decisions - Li, Pengfei; Wang, Zhengwei (Asian Economic and Financial Review, 2018)
Household leverage has significant influence on their stock market investment decisions, controlling for age, gender, wealth, income, education background, and financial experience. Using a unique survey data in China, we provide evidence that individuals with higher household leverage are less likely to participate on the stock market. However, for stock market participators, higher household leverage is associated with higher investment rate on stocks and mutual funds. We further examine the underlying mechanisms by financial constraint and risk aversion. Financial constraint cannot explain the effect of leverage on respondents’ stock market participation, but is a good moderator variable for the influence of leverage on participators’ stock investment rate. The enhancement effect of leverage on the stock investment rate is stronger for the stock market participators when they face less severe financial constraint. Risk preference can help explain the household leverage effect. The impediment effect of household leverage on stock market participation only works when they are strongly risk averse while the enhancement effect of household leverage on stock investment rate only works when participators are slightly risk averse.